Asymptotic expansion in approximation by normal law - Bikelis, Algimantas; Augutis, Juozas; Padvelskis, Kazimieras (Lietuvos matematikos rinkinys, 2011)
We consider the asymptotic behavior of the convolution P*n(A\sqrt{n}) of a k-dimensional probability distribution P(A) as n → ∞ for A from the σ-algebra M of Borel subsets of Euclidian space Rk or from its subclasses.
Keywords: probability distributions in R^k,; convolutions; Bergström identity; Appell polynomials; Chebyshev–Cramer asymptotic expansion